The borderline state commemorative practices in Russian-controlled territories, 2022–2023 - Homanyuk, Mykola 1974-; Gabowitsch, Mischa 1977- (2024)
The article provides a concise overview of the Russian invaders’ interactions with war memorials in the occupied parts of Ukraine. Since the first days of the fullscale invasion of Ukraine, the Russian forces and proxy administrators have focused significant attention on war memorials in the newly occupied territories. They have claimed that World War II memorials in Ukraine have been either completely destroyed or left to decay. In reality, local residents in the northern, eastern and southern regions of Ukraine have often integrated Soviet-era memorials into the new Ukrainian national memorial canon and folk religious memorial practices in recent decades. Local residents have domesticated Soviet-era war memorials by installing additional, personal memorial signs and plaques, or by bringing religious symbols and objects to the sites. Since the beginning of the aggression in 2022, the most prevalent way in which the occupiers have interacted with war memorials has been by lighting eternal flames or marking existing memorials with Russian or Soviet symbols. In addition, they have engaged in iconoclastic practices, such as removing Ukrainian national symbols from the memorials. At the same time, World War II memorials have frequently served as venues for a variety of public events since 2022, ranging from legitimising the ongoing war to showcasing the commemorative efforts of diverse activists, including collaborators and political parties. As the Armed Forces of Ukraine have entered liberated territories, they have frequently singled out such monuments to install Ukrainian symbols, signifying the de-occupation of both these monuments and the lands. The comparatively few Ukrainian initiatives to have war memorials removed have been responses to Russia’s use of such memorials as pretexts for invasion